Cancer Metaphors : A Sociocultural Perspective Study of Cancer Patient Narratives - Liaw, Monica Kah Pei (Universiti Malaysia Sarawak (UNIMAS), 2021)
Cancer is a complex disease that is usually difficult to talk about. Many cancer patients turn to metaphors to describe the disease and their cancer experiences as this allows them to communicate those experiences more effectively. This study sought to examine the metaphors used by cancer patients when describing the disease and their cancer experiences. Most importantly, the study aimed to investigate how these metaphors are shaped by the patients’ sociocultural background, understanding and perception. Using the Metaphorical Identification Procedure (MIP) and Lexical Concepts, Cognitive Models and Meaning-Constructions (LCCM) theory, the study analysed the data collected from 31 cancer patients from Kuching, Sarawak through semi-structured interview. The results showed that the patients turned to “structural”, “conspiracy” and “journey” metaphors more than other metaphors to describe the disease and their cancer experiences. Besides, female cancer patients used more metaphors compared to male and the choices of metaphors are also different across ethnic groups. The findings suggest that cancer patients were most likely to use and interpret the metaphors in ways that supported by their own sociocultural systems and value schemata. The LCCM analysis through the Unified Framework of Analysis showed that the cancer metaphors used by these patients were mostly shaped by their personal life experiences and their sociocultural understanding. The study concluded that the findings could have implications on the current debates over the use of cancer metaphors in and it could help to drive some recommendations for future research.